PELATIHAN DAN PENDAMPINGAN PENGELOLAAN ADMINISTASI BUMDES DI DESA ELLAK DAYA KECAMATAN LENTENG - Dwi Listia Rika Tini; Roos Yuliastina (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2021)
BUMDes Assalam in Ellak Daya village has been one year operated in futsal field rent sector and permanent shop rent, and also develope bumdes galery effort to sell harvest and society UMKM ptoduct. For improving bumdes developing in village economy effort, so we need processing sistem management, because this time the bumdes doesn't have administration standart in managing bumdes. The method is used in this activity are lecture, demonstrations, questions and answers. The result that is reached after this training is: (1) BUMDes Assalam manager master manage the file based on computer; (2) BUMDes Assalam manager can arrange finance sop from futsal field rent and shop; (3) BUMDes administrator have a good understanding about duty and the function; (4) BUMDes Assalam manager can arrange a good accounting report and administration noting so they can give administrator responsibility in using the fund of capital partisipation that has given by giverment.